EXPLORING MADRASSA EDUCATION WITH REFERENCE TO CHILD RIGHTS IN PAKISTAN - Ahmed, Mr. Naveed; Shah, Dr. Rehmat; Minaz, Dr. Maksal; Hussain, Dr. Sajjad (The journal of contemporary issues in business and government, 2021)
Education is the main pillar for the development of a country. Madrassa education systems have a sensitive and important role in Pakistan. This system produces religious leaders whom peoples follow as spiritual leaders, but the international world has different perceptions about Madrassa. The purpose of this study was to explore how Madrassa management implements the student’s rights and what are the causes of violation of student’s rights in Madrassa. This study was qualitative in nature to understand in-depth knowledge of Madrassa education phenomena. The population of the study was students and teachers of the Madrassa education system. The samples of the study were 08 students and 08 teachers of Madrassas from district Rawalpindi and a purposive sampling technique was used for the study. Data was collected personally through semi-structured interviews. The data was analyzed using the direct quotation method. The findings of the study demonstrate that Madrassa systems have limited sources and government does not own Madrassa like a public institution, so Madrassa has a lot of barriers in the implementation of children's rights. The staff of Madrassa education without professional development is the cause of violation of child’s rights. Government should provide funding and other facilities to Madrassa like public educational institutions and reforms should bring after holding the trust of Madrassa stakeholders.